2016
DOI: 10.1590/s1677-5538.ibju.2015.0608
|View full text |Cite
|
Sign up to set email alerts
|

Extraperitoneal versus transperitoneal laparoscopic radical cystectomy for selected elderly bladder cancer patients: a single center experience

Abstract: Objective:This study reports the initial experience of extraperitoneal laparoscopic radical cystectomy (ELRC) and compared with transperitoneal laparoscopic radical cystectomy (TLRC) in the treatment of selected elderly bladder cancer patients.Patients and Methods:A total of forty male bladder cancer patients who underwent ELRC (n=19) or TLRC (n=21) with ureterocutaneostomy were investigated. Demographic parameters, perioperative variables, oncological outcomes and follow-up data were retrospectively analyzed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
1
6
0
3
Order By: Relevance
“…Therefore, maintaining the integrity of the peritoneum is an effective way to reduce the adverse consequences of urine or intestinal leakage. It is worth noting that in previous studies, it was recommended that the peritoneum should be removed with the bladder wall when the tumors were located at the bladder apex or the posterior bladder wall to ensure the safety of the oncology results, and then the peritoneum was closed [7]. In addition, it has been reported that the possibility of peritoneal involvement in T1-T2 bladder cancer patients is extremely low [33], which was also observed in this study.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Therefore, maintaining the integrity of the peritoneum is an effective way to reduce the adverse consequences of urine or intestinal leakage. It is worth noting that in previous studies, it was recommended that the peritoneum should be removed with the bladder wall when the tumors were located at the bladder apex or the posterior bladder wall to ensure the safety of the oncology results, and then the peritoneum was closed [7]. In addition, it has been reported that the possibility of peritoneal involvement in T1-T2 bladder cancer patients is extremely low [33], which was also observed in this study.…”
Section: Discussionsupporting
confidence: 60%
“…The trocar setting of the ELRC was identical to the one described by Lang et al [7]. The space between the laterovesical peritoneum and the external iliac vessels was separated upward along the right side of the bladder neck to the internal inguinal ring.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…Furthermore, identification of the peritoneal reflex at the top of the bladder and mobilizing the peritoneum that covers the posterosuperior surface of the bladder is an additional relatively difficult step. It has previously been reported that the peritoneum can be removed together with the bladder 20 . In our experience, after cutting the median ligament of the umbilical cord, engaging an assistant to help lift the bladder upwards in addition to pressing down on the peritoneum is a significant detail in this procedure.…”
Section: Discussionmentioning
confidence: 85%
“…As shown in literature, the final step of ELRC is to separate the bladder and peritoneum [ 17 ]. With early return of peristalsis, the incidence of postoperative ileus would be lower, mainly attributed to opening the peritoneum late and close the peritoneum promptly after establishing a neobladder [ 6 ].…”
Section: Discussionmentioning
confidence: 99%